The Causative factors of failure among undergraduate Malaysian students in Al-Azhar University: a qualitative case study - Abd Razak, Afareez; Razikin, Mohyani; Abdul Rahman, Nik Suryani; Sheikh Ahmad, Ismail (2010)
Purpose: A worrying number of Malaysian undergraduate students are failing in Al-Azhar University annually. This qualitative case study looks into the reasons behind why a large number of Malaysian students fail. It is to understand and add to our knowledge of the reasons of why this phenomenon is occurring. The study aims to identify what seem to be the contributing factors which cause the Malaysian students to fail in their examinations; based on previous literature, what would be the consequences of not having adequate mastery of Arabic language while studying in a particular setting; and in what could the factors contributing to failure be overcome or minimized.